HIC1 suppresses Tumor Progression and Enhances CD8+ T Cells Infiltration Through Promoting GSDMD‐induced Pyroptosis in Gastric Cancer - Mengjie Kang; Wenqi Du; Lina Ding; Mengdi Wu; Dongsheng Pei (Advanced Science)
Abstract Recently, immune checkpoint blockade treatment has made remarkable strides in combatting malignancies, including gastric cancer (GC). Nonetheless, the efficacy of immunotherapy in GC patients remains constrained, warranting further exploration of the underlying molecular mechanisms to improve therapeutic outcomes. Hypermethylated in cancer 1 (HIC1) is acknowledged as a transcriptional regulator crucial for multiple aspects of cell development, yet its role in antitumor immune responses remains incompletely understood. This investigation reveals a significant downregulation of HIC1 in gastric cancer, correlating with a less favorable prognosis. Overexpression of HIC1 promotes the initiation of cell pyroptosis. Mechanistically, gasdermin D (GSDMD), a pivotal executor of pyroptosis, is identified as a downstream target of HIC1 and activated by HIC1 at the transcriptional level. Subsequent cleavage of the GSDMD N‐terminal region punctures the cell membrane, instigating pyroptosis and releasing inflammatory factors. Furthermore, HIC1 augments the infiltration of CD8+ T cells to counteract immune evasion. The combinatorial approach of HIC1 overexpression with PD‐L1 antibody demonstrates a synergistic therapeutic impact in treating GC. Additionally, c‐Jun activation domain‐binding protein 1 (Jab1) mediates the ubiquitylation and proteasomal degradation of HIC1 at Lys517. Ultimately, these findings underscore the potential of HIC1 as a promising immunotherapeutic target for the treatment of GC.